Labor Market Concentration and Wages: Incumbents versus New Hires - Andrea Bassanini; Cyprien Batut; Eve Caroli (Institute of Labor Economics (IZA), 2023)
We investigate the impact of labor market concentration on average wages and decompose it into its effects on new hires and incumbents, where incumbents are defined as individuals who were already employed in the same firm the year before. Using administrative data for France, we find that concentration negatively affects both new hires' and incumbents' wages with elasticities ranging from -0.0287 to -0.0296 and -0.0185 to -0.0230, respectively. It also reduces the probability that a worker be a new hire rather than an incumbent. When decomposing the overall effect of labor market concentration on wages into its different components, we find that the negative effect on incumbents' wages accounts for between two thirds and three fourth of the total.
Keywords: J31; J42; L41; 330; labor market concentration; monopsony; wages; incumbents